Research Advances on Biosynthesis, Regulation, and Biological Activities of Apocarotenoid Aroma in Horticultural Plants - Jianan Shi; Chao Cao; Jiayu Xu; Chunhua Zhou (Journal of Chemistry)
Apocarotenoids, which play important roles in the growth and development of horticultural plants, are produced by the action of carotenoid cleavage oxygenase (CCO) family members or nonenzymatic cleavage actions. Apocarotenoids are commonly found in leaves, flowers, and fruits of many horticultural plants and participate in the formation of pigments, flavors, hormones, and signaling compounds. Some of them are recognized as important aroma components of fruit and flower with aromatic odor, such as βß-ionone, β-damascenone, and 6-methyl-5-hepten-2-one in tomato fruit, and have low odor thresholds with β-ionone having odor threshold of only 0.007 ppb. In this review, the main apocarotenoid aroma components in horticultural plants were listed, and factors influencing their production were discussed at first. Then, the biosynthetic pathway of apocarotenoid aromas was briefly introduced, and the CCDs gene family was highlighted, and the nonenzymatic production of apocarotenoid aromas was also mentioned. Next, chemical and molecular regulations of apocarotenoid aromas and their biological activities were summarized. Finally, further exploration aspects needed were suggested. We anticipate that this review can afford some crucial information for comprehensive application of apocarotenoid volatile compounds in horticultural plants.